2019
DOI: 10.32598/jpcp.7.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Internet Addiction in Medical Students by General Self-efficacy, Difficulty in Emotion Regulation, and Resilience

Abstract: The present study aimed to predict internet addiction based on general self-efficacy, difficulty in emotion regulation, and resilience in medical students. Methods: This was a cross-sectional study. The statistical population included all medical students of Shahid Beheshti University of Medical Sciences. The research sample consisted of 96 medical students selected by random sampling method in 2018. Data collection was performed by Sherer General Self-Efficacy Scale, Gramat's and Roemer's Difficulties in Emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is no surprise, then, that left-behind children generally show characteristics of a lack of resilience and heightened psychological vulnerability, and are more likely to demonstrate barriers against internalization and lower self-esteem and self-efficacy (Hetherington et al, 1998). In a sample of 96 medical students, Ebrahimi et al (2019) reported that resilience was related with general self-efficiency (r ¼ .57). As this issue is so prevalent in the Chinese context, it is important to be able to effectively measure the resilience of the leftbehind children in China.…”
Section: Introductionmentioning
confidence: 99%
“…It is no surprise, then, that left-behind children generally show characteristics of a lack of resilience and heightened psychological vulnerability, and are more likely to demonstrate barriers against internalization and lower self-esteem and self-efficacy (Hetherington et al, 1998). In a sample of 96 medical students, Ebrahimi et al (2019) reported that resilience was related with general self-efficiency (r ¼ .57). As this issue is so prevalent in the Chinese context, it is important to be able to effectively measure the resilience of the leftbehind children in China.…”
Section: Introductionmentioning
confidence: 99%
“… Effect size for the relationship between PIU and resilience [ 33 , 34 , 35 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. …”
Section: Figurementioning
confidence: 99%
“…According to Poormahdy et al (2022), tobacco addiction can also increase with an effect on cognitive awareness for individuals who experience difficulty regulating their emotions. The literature has shown that positive relationships can exist between emotion regulation difficulties and Internet addiction (Salek Ebrahimi et al, 2019;Sertbaş et al, 2020). Other studies have suggested that emotion regulation strategies predict Internet addiction at a significant level, with a negative relationship between emotion regulation strategies and Internet addiction (Amendola et al, 2019;Amiri et al, 2015;Ateş & Sağar, 2021;Oktan, 2011;Trumello et al, 2018;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%